Исследование структурных превращений и их влияние на поверхностный слой при зубошлифовании - Степанов, Михаил Сергеевич; Клочко, Александр Александрович; Анцыферова, Олеся Александровна (НТУ "ХПИ", 2015)
Одним из основополагающих факторов обеспечения высокой долговечности закаленных зубчатых колес является изучение состояния напряжений в поверхностном слое, определяющимися видом и условиями технологического воздействия в процессе зубошлифования. Рассмотрено влияние остаточных напряжений на прочность зубчатых колес в зависимости от тепла, возникающем в зоне резания и приводящие к образованию растягивающих напряжений, изменению твердости и структуры. Причиной структурных напряжений являются изменения объема по сечению материала, вызванные превращением аустенита меньшего удельного объема в структуре большего удельного объема.

A fundamental factor of high durability hardened toothed wheels are an investigation of the stresses in the surface layer, is determined by the type and conditions of technological impact in the process of disease. The influence of residual stresses on durability of gears depending on heat generated in the cutting zone and leads to the formation of tensile stresses, the change of hardness and structure. Cause structural stresses are volume changes in the cross section of the material caused by the transformation of austenite to smaller specific volume in the structure of the higher specific volume. Structural residual stresses in the surface layer of the toothed wheels with different schemes of disease always appear in conjunction with thermal stress and causes the tensile stress, and at the core of compressive stress.
Study of structural transformations and their effect on the surface layer when the grinding
Keywords: воздействие технологическое; колесо зубчатое; напряжение; круг абразивный; surface layer; technological exposure; tempered gear